A Behavioral analysis of nurses' and pharmacists' role in addressing vaccine hesitancy: scoping review. Issue 11 (2nd November 2021) - Cassidy, Christine; Langley, Jodi; Steenbeek, Audrey; Taylor, Beth; Kennie-Kaulbach, Natalie; Grantmyre, Hilary; Stratton, Lillian; Isenor, Jennifer
ABSTRACT: The purpose of this review was to identify, characterize, and map the existing knowledge on a) nurses' and pharmacists' perceived barriers and enablers to addressing vaccine hesitancy among patients; and b) strategies or interventions for nurses and pharmacists to address vaccine hesitancy in their practice. Our comprehensive search strategy targeted peer-reviewed and grey literature. Two independent reviewers screened papers and extracted data. We coded narrative descriptions of barriers and enablers and interventions using the Behavior Change Wheel. Sixty-six records were included in our review. Reported barriers (n = 9) and facilitators (n = 6) were identified in the capability, opportunity and motivation components. The majority of the reported interventions were categorized as education (n = 47) and training (n = 26). This current scoping review offers a detailed behavioral analysis of known barriers and enablers for nurses and pharmacists to address vaccine hesitancy and interventions mapped onto these behavioral determinants.